Media and social conflicts during the covid-19 pandemic: analysis of the approaches present in the Lima press during the protests against the interim government of Manuel Merino (2020) - Angulo-Giraldo, Miguel (2021)
Latin America experienced a series of massive social demonstrations in recent years with different political repercussions. In Peru, between October and November 2020, 13% of Peruvians mobilized in the streets due to a social conflict caused by the vacancy of President Martín Vizcarra and the appointment of a new president. The Peruvian media put this situation on the agenda; However, a difference was evidenced in the way of approaching this conflict and interpreting it towards citizens. From a descriptive, cross-sectional, non-experimental and mixed approach, 53 front pages of the most consumed newspapers in Peru (El Comercio, La República, Trome and El Popular) are analyzed, from which the majority presence of a journalistic approach of threat and opposition, and the null appearance of a frame that promotes dialogue in order to transform said conflict.